Statistical Analysis of Ceiling and Floor Effects in Medical Trials - Janan Arslan; Kurt Benke (Applied Biosciences, 2023)
Exploratory data analysis and statistical moments were used to investigate the potential impact of ceiling and floor effects in medical trials. A total of 150 treatment-naive eyes were assessed in a retrospective case study of patients who were treated with anti-VEGF injections for wet age-related macular degeneration. The experimental results revealed that ceiling and floor effects are problematic in data analysis and may result in serious errors when using standard parametric tests. The case study provided insights relating to methodology in medical trials, experimental data analysis, and statistical inference, as applied to the interpretation of treatment response limits. Suggestions are provided for statistical data pre-processing and post-processing when significantly skewed distributions are present in response groups.